A New Simpler Third-Order Chaotic System and its Circuit Implementation. Issue 2 (2nd April 2016) - Fei, Li; Aina, Qin
Abstract: This paper introduces a relatively simple three-dimensional chaotic system, which has only two equilibrium points. The system is theoretically demonstrated to be chaotic by calculation of the Lyapunov exponents and stability analysis of the equilibrium points. Then, the bifurcation diagram of the system is given to observe its period-doubling phenomenon. Compared with the Rössler system, the structure of the new system is more simple, only one nonlinear product term and two parameters. Finally, an analog electronic circuit is designed to realize the system, the simulation result is achieved and basic dynamical behaviors are briefly described.